Artificial Intelligence in Cable Fault Detection and Localization: Recent Advances and Research Challenges - Qianqiu Shao; Songhai Fan; Zongxi Zhang; Fenglian Liu; Zhengzheng Fu; Pinlei Lv; Zhou Mu (Energies, 2025)
With the large-scale integration of new power systems and distributed generators (DGs), cable fault detection and localization face numerous challenges, where artificial intelligence (AI) techniques demonstrate significant advantages. This review first outlines the causes of cable faults and traditional methods for fault detection and localization. Subsequently, it comprehensively analyzes the applications of both conventional machine learning and deep learning approaches in this field, elaborating on their application scenarios, strengths, defects, and successful case studies, providing valuable references for researchers and professionals. Additionally, the paper discusses the strengths and limitations of current AI techniques, along with the impacts introduced by DG integration. Finally, it highlights future development trends and potential research directions for advancing AI-based solutions in cable fault detection and localization.